Application of Ultrasonic Atomization in the Three Dimensional Printing and Spray Pyolysis - Zhou, Yufeng (2016)
Control of droplet size and distribution, jettability of fluid with high viscosity and surface tension, microfeeding to solid particles are important problems in the three dimensional printing. Meanwhile, spray pyrolysis technique has been used to produce film or nanoparticle synthesis. In this paper, the application of ultrasonic atomization in these new fields has been reviewed. The principle of atomization was introduced, and the current performance in comparison to conventional approaches was summarized. Overall, ultrasonic atomization could generate small droplets with a narrow distribution at a low power, liquid with high viscosity and surface tension can also be ejected under ultrasound excitation. Nozzle design should be optimized for higher efficiency.